Perancangan dan Implementasi Video Profil Sekolah SMK Al-Azhar Batam menggunakan MDLC - Muhammad Ardiansyah; Willy Fernando (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2022)
Video marketing is a great way to increase business results. Video Marketing presents an opportunity for businesses to stir emotions and appeal to the needs of their audience. This study describes the process of making promotional videos to introduce facilitation, accreditation to achievements that have been achieved by SMA Al-Azhar Batam. By utilizing multimedia developments such as visual effects, it is hoped that it will attract more attention and facilitate the delivery of messages from this video. In the process of making promotional videos using Adobe Premiere Pro 2020 and Filmora software. Making this video through the process of observation and interviews with the school. The results of these observations and interviews produce outputs in the form of video marketing that will help the school to promote activities in the school environment. Video marketing is made using motion graphics methods so as not to watch and attract public interest in schools.